Library Services Quality Evaluation at the Balai Layanan Perpustakaan DPAD DIY with Integration Analysis Using the Libqual Model and Importance Performance Analysis (IPA) Method - Ndaru Ramadhan; Jovanscha Qisty Adinda FA; Ida Widianingsih (Dinasti Publisher, 2024)
Balai Layanan Perpustakaan DPAD DIY is the unit that implements library material services to improve the library services quality. Balai Layanan Perpustakaan DPAD DIY has various library services to carry out its duties and responsibilities. The provision of library services must be oriented towards community satisfaction. So, the aim of this research is to measure the extent to which the library services quality at the Balai Layanan Perpustakaan DPAD DIY uses a new method, namely the integration of the Libqual model and the IPA method. This research also aims to identify influencing factors in the quality of library services and prepare recommendations for improvement. This research uses four dimensions and 26 indicators of the Libqual model to measure service quality. The results show that the average level of suitability of library services quality is 96.19%, and the average level of discrepancy is -0.13. This indicates that the performance of library services still needs to meet community expectations. Next, the result of the IPA analysis is some indicators require quality improvement, namely the Personal Control indicators (PC3, PC5, and PC6) and Information Access (IA1 and IA4), even though they are not the main priority.